Epitope mapping of severe acute respiratory syndrome coronavirus 2 neutralizing receptor binding domain-specific monoclonal antibodies - Maghsood, Faezeh; Amiri, Mohammad Mehdi; Zarnani, Amir-Hassan; Salimi, Vahid; Kardar, Gholam Ali; Khoshnoodi, Jalal; Mobini, Maryam; Ahmadi Zare, Hengameh; Ghaderi, Abbas; Jeddi-Tehrani, Mahmood; Schmidt, Sylvie; Laumond, Géraldine; et al. (Frontiers in Medicine, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the causative agent of the outbreak led to the coronavirus disease 2019 (COVID-19) pandemic. Receptor binding domain (RBD) of spike (S) protein of SARS-CoV-2 is considered as a major target for immunotherapy and vaccine design. Here, we generated and characterized a panel of anti-RBD monoclonal antibodies (MAbs) isolated from eukaryotic recombinant RBD-immunized mice by hybridoma technology. Epitope mapping was performed using a panel of 20-mer overlapping peptides spanning the entire sequence of the RBD protein from wild-type (WT) Wuhan strain by enzyme-linked immunosorbent assay (ELISA). Several hybridomas showed reactivity towards restricted RBD peptide pools by Pepscan analysis, with more focus on peptides encompassing aa 76-110 and 136-155. However, our MAbs displaying potent neutralizing activity by blocking SARS-CoV-2 spike pseudovirus entry to angiotensin-converting enzyme-2 (ACE2) expressing HEK293T cells as well as the wild-type virus showed no reactivity against these peptides. These findings, largely supported by the Western blotting results suggest that the neutralizing MAbs recognize mainly conformational epitopes. Moreover, our neutralizing MAbs recognized the variants of concern (VOC) currently in circulation, including alpha, beta, gamma, and delta by ELISA, and neutralized alpha and omicron variants at different levels by conventional virus neutralization test (CVNT). While the neutralization of MAbs to the alpha variant showed no substantial difference as compared with the WT virus, their neutralizing activity was lower on omicron variant, suggesting the refractory effect of mutations in emerging variants against this group of neutralizing MAbs. Also, the binding reactivity of our MAbs to delta variant showed a modest decline by ELISA, implying that our MAbs are insensitive to the substitutions in the RBD of delta variant. Our data provide important information for understanding the immunogenicity of RBD, and the potential application of the novel neutralizing MAbs for passive immunotherapy of SARS-CoV-2 infection.